The evolutionary origins of diadromy inferred from a time-calibrated phylogeny for Clupeiformes (herring and allies) - Bloom, Devin D. (The Royal Society, 2014)
One of the most remarkable types of migration found in animals is diadromy, a life-history behaviour in which individuals move between oceans and freshwater habitats for feeding and reproduction. Diadromous fishes include iconic species such as salmon, eels and shad, and have long fascinated biologists because they undergo extraordinary physiological and behavioural modifications to survive in very different habitats. However, the evolutionary origins of diadromy remain poorly understood. Here, we examine the widely accepted productivity hypothesis, which states that differences in productivity between marine and freshwater biomes determine the origins of the different modes of diadromy. Specifically, the productivity hypothesis predicts that anadromous lineages should evolve in temperate areas from freshwater ancestors and catadromous lineages should evolve in tropical areas from marine ancestors. To test this, we generated a time-calibrated phylogeny for Clupeiformes (herrings, anchovies, sardines and allies), an ecologically and economically important group that includes high diversity of diadromous species. Our results do not support the productivity hypothesis. Instead we find that the different modes of diadromy do not have predictable ancestry based on latitude, and that predation, competition and geological history may be at least as important as productivity in determining the origins of diadromy.